The association between non-HDL cholesterol and SYNTAX score in premature heart disease - Hakan Şahin; Ersan Oflar; Cennet Yıldız; İsmail Ungan; Veli Polat; İbrahim Faruk Aktürk (National Scientific Medical Center, 2022)
Aim: This study aimed to estimate the association of coronary artery disease complexity with non-HDL-C levels in premature CAD. Background: Primary prevention has utmost importance in terms of minimizing the number of patients who had premature coronary artery disease (CAD). Non-high density lipoprotein cholesterol (non-HDL-C) contains potentially atherogenic lipoprotein fractions. Material and methods: Coronary angiographic recordings of two hundred acute coronary syndrome patients were evaluated by two cardiologists. Clinical, demographic and lipid parameters of the patients were compared with SYNTAX score. Results: Median age of the study group was 41 (18-45) years. One hundred eighty five (90.5%) of them were male, nineteen (9.5%) of them were female. Median SYNTAX score and ejection fraction of the patients were 17 (4.5-39) and 50 (33-68), respectively. SYNTAX score of the male patients was significantly higher compared to females [17 (4.5-39) vs 12 (8-26), p=0.048), similarly, diabetic patients had higher values of syntax score compared to non-diabetic patients [19 (10-39) vs 16 (4.5-37), p=0.005), There were no differences of SYNTAX score with respect to presence of hypertension, smoking status and family history of CAD.  There were very strong positive correlation between SYNTAX score and non-HDL-C, TC and LDL-C levels (r=0.958, r=0.946 and r=0.921, respectively, p<0.001 for all).   HgA1c levels showed positive correlation, whereas HDL-C showed negative correlation with SYNTAX score (r=0.793 and r=-0.620, respectively, p<0.001 for both). Conclusion: non-HDL-C was a valuable tool in assessing the complexity of atherosclerotic cardiovascular disease in young patients.